2018
DOI: 10.1039/c8py01011k
|View full text |Cite
|
Sign up to set email alerts
|

Photolatent ring-opening metathesis polymerization in miniemulsion: a powerful approach to produce polynorbornene latexes

Abstract: The use of miniemulsion Ring-Opening Metathesis Polymerization (ROMP) to form polyunsaturated latexes is still a largely unexplored field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…In this study, all the miniemulsions were performed in a photo-reactor equipped with an airtight sonication probe and prepared with a dispersed phase content of 10 w/w % following a process similar to that previously described 19 D: the average diameter, σ: the standard deviation.…”
Section: 3-nb Miniemulsion Rompmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, all the miniemulsions were performed in a photo-reactor equipped with an airtight sonication probe and prepared with a dispersed phase content of 10 w/w % following a process similar to that previously described 19 D: the average diameter, σ: the standard deviation.…”
Section: 3-nb Miniemulsion Rompmentioning
confidence: 99%
“…Nb conversion reached only 36 % after 60 min ( Figure 2 blue curve) which is comparable to the conversion obtained in the previous study. 19 Scheme 1: Formation of PNb latex Sonication 2 min initial droplet size sonication 2 min final particle size sonication 10 min initial droplet size Sonication 10 min final particle size analyses (Table 1). For all polymer samples, experimental average molar masses were much higher than the theoretical ones, indicating a poor initiation efficiency of the polymerization.…”
Section: 1-miniemulsion Romp In Annular Reactormentioning
confidence: 99%
See 1 more Smart Citation
“…[27] Pichavant et al also recently reported a different approach to overcome the inherent problem of high catalyst activity in the miniemulsion at room temperature by designing a photolatent ROMP catalytic system. [28] They demonstrated the successful preparation of stable PNB latexes (≈100 nm particle diameter) using catalysts based on a N-heterocyclic carbene (NHC) photogenerating system.…”
Section: Block Copolymersmentioning
confidence: 99%
“…Using this catalyst it was possible to develop a robust procedure to obtain stable latexes of PCOD and PNB, with particles in the range from 100 to 300 nm, with ≈100% conversion and relative short times, using either ionic or nonionic surfactants . Pichavant et al also recently reported a different approach to overcome the inherent problem of high catalyst activity in the miniemulsion at room temperature by designing a photolatent ROMP catalytic system . They demonstrated the successful preparation of stable PNB latexes (≈100 nm particle diameter) using catalysts based on a N‐heterocyclic carbene (NHC) photogenerating system.…”
mentioning
confidence: 99%